2009
DOI: 10.1016/s0924-9338(09)71128-9
|View full text |Cite
|
Sign up to set email alerts
|

Maintained Attitudinal Changes in Nursing Personnel After a Brief Training on Suicide Prevention

Abstract: Aim:To verify whether nursing personnel working at a general hospital change their attitudes after a brief training course on suicide prevention and if these newly acquired attitudes persist over a 6-month time.Method:317 nursing personnel attended a 6-hour training program. They answered anonymously pre- and post-training the Suicide Behavior Attitude Questionnaire (SBAQ) which comprises 21 visual analogue scale items divided in three factorial sub-scales. The scores on each SBAQ sub-scale (dependent variable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 0 publications
3
14
0
2
Order By: Relevance
“…In this study, lower perception of self-perception of professional competence and more negative feelings towards the patient mutually reinforced each other, a finding that was particularly notable among professionals with lower qualifications or less work experience (the assistant nurses group and the group without suicide/mental health training or experience). Only the association between training and self-perception of professional competence is similar to the outcomes of other Brazilian studies conducted with nursing personnel working at a general hospital that received training (Botega et al, 2007), nursing students after a training course (Bott et al, 2015) and nursing undergraduates who participated in psychiatric nursing disciplines, classes or laboratory about suicide (Moraes et al, 2016). Some of these studies also identified an association between training and less negative attitudes (Botega et al, 2007;Bott et al, 2015).…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…In this study, lower perception of self-perception of professional competence and more negative feelings towards the patient mutually reinforced each other, a finding that was particularly notable among professionals with lower qualifications or less work experience (the assistant nurses group and the group without suicide/mental health training or experience). Only the association between training and self-perception of professional competence is similar to the outcomes of other Brazilian studies conducted with nursing personnel working at a general hospital that received training (Botega et al, 2007), nursing students after a training course (Bott et al, 2015) and nursing undergraduates who participated in psychiatric nursing disciplines, classes or laboratory about suicide (Moraes et al, 2016). Some of these studies also identified an association between training and less negative attitudes (Botega et al, 2007;Bott et al, 2015).…”
Section: Discussionsupporting
confidence: 80%
“…Only the association between training and self-perception of professional competence is similar to the outcomes of other Brazilian studies conducted with nursing personnel working at a general hospital that received training (Botega et al, 2007), nursing students after a training course (Bott et al, 2015) and nursing undergraduates who participated in psychiatric nursing disciplines, classes or laboratory about suicide (Moraes et al, 2016). Some of these studies also identified an association between training and less negative attitudes (Botega et al, 2007;Bott et al, 2015).…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Effective training in suicide awareness and prevention has been described in several settings and several programmes and courses exist at individual, group and organisational levels. The concept of mental health first aid (MHFA) training arose in Australia in 2001, as a means of training the public to help adults with mental health problems including suicide, and now exists in several countries and settings, including the workplace.…”
Section: Suicide Awareness and Mitigation Trainingmentioning
confidence: 99%